Dynamic formation of asexual diploid and polyploid lineages: multilocus analysis of Cobitis reveals the mechanisms maintaining the diversity of clones - Janko, Karel; Kotusz, Jan; De Gelas, Koen; Slechtová, Vera; Opoldusová, Zuzana; Drozd, Pavel; Choleva, Lukáš; Popiołek, Marcin; Baláž, Marián (PloS one, 2012)
Given the hybrid genomic constitutions and increased ploidy of many asexual animals, the identification of processes governing the origin and maintenance of clonal diversity provides useful information about the evolutionary consequences of interspecific hybridization, asexuality and polyploidy. In order to understand the processes driving observed diversity of biotypes and clones in the Cobitis taenia hybrid complex, we performed fine-scale genetic analysis of Central European hybrid zone between two sexual species using microsatellite genotyping and mtDNA sequencing. We found that the hybrid zone is populated by an assemblage of clonally (gynogenetically) reproducing di-, tri- and tetraploid hybrid lineages and that successful clones, which are able of spatial expansion, recruit from two ploidy levels, i.e. diploid and triploid. We further compared the distribution of observed estimates of clonal ages to theoretical distributions simulated under various assumptions and showed that new clones are most likely continuously recruited from ancestral populations. This suggests that the clonal diversity is maintained by dynamic equilibrium between origination and extinction of clonal lineages. On the other hand, an interclonal selection is implied by nonrandom spatial distribution of individual clones with respect to the coexisting sexual species. Importantly, there was no evidence for sexually reproducing hybrids or clonally reproducing non-hybrid forms. Together with previous successful laboratory synthesis of clonal Cobitis hybrids, our data thus provide the most compelling evidence that 1) the origin of asexuality is causally linked to interspecific hybridization; 2) successful establishment of clones is not restricted to one specific ploidy level and 3) the initiation of clonality and polyploidy may be dynamic and continuous in asexual complexes.
Keywords: Microsatellite Repeats; mikrosatelitní repetice; Animals; Cypriniformes; genotyp; DNA, Mitochondrial; Genotype; Polyploidy; polyploidie; Diploidy; zvířata; mitochondriální DNA; diploidie; máloostní